Pendugaan Umur Simpan Produk Pastry dengan Quantitative Descriptive Analysis (QDA) dan Metode Arrhenius - Dase Hunaefi; Fitriyah Ulfah (Jurnal Mutu Pangan : Indonesian Journal of Food Quality, 2019)
The Unclear and limited shelf-life of pastry become the problem for SMEs. The objective of the study was to determine shelf-life using sensory evaluations by Quantitative Descriptive Analysis (QDA). The fresh pastries are Croissants with chocolate and cheese fillings and also in Apple Danishes. As a supporting data, proximate analysis was done on the three samples. The rancidity analysis was done using the Thiobarbituric Acid (TBA) method to measure the malondialdehyde level. TBA method was conducted. Determination of shelf-life Sensory evaluations was performed by ten trained panelists analysed sensory characteristic changes during storage. The sensory characteristics identified were taste, aroma, rancidity, hardness, crust and crumb, and the filling consistency changes during storage. Shelf-life apple danish, chocolate croissant and cheese croissant by QDA in a row were 6, 6 and 5 days. Meanwhile, Arrhenius method showed that fresh pastries have much longer shelf-life. Shelf-life Apple danish, chocolate croissant and cheese croisaant by Arrhenius method were 48, 35 and 48 days, respectively. Therefore, in the case of shelf-life prediction of pastries, QDA method resulted better accurate method in prediction of shelf-life.